Laser-Based Devices for Female Genitourinary Indications: Position Statements From the European Society for Sexual Medicine (ESSM). Issue 5 (19th March 2020) - Romero-Otero, Javier; Lauterbach, Roy; Aversa, Antonio; Serefoglu, Ege Can; García-Gómez, Borja; Parnham, Arie; Skrodzka, Marta; Krychman, Michael; Reisman, Yacov; Corona, Giovanni; Lowenstein, Lior
Abstract: Background: Laser-based technologies have been commercially marketed as "wonder treatments" without a sufficient and adequate body of evidence. In addition, on July 30, 2018, the U.S. Food and Drug Administration issued a warning regarding the safety of the use of laser-based devices for the following indications: vaginal "rejuvenation" or cosmetic vaginal procedures, vaginal conditions and symptoms related to menopause, urinary incontinence, and sexual function. Aim: To perform a thorough review of the available literature regarding laser-based vaginal devices for the treatment of female genitourinary indications and summarize the results in several short statements according to the level of evidence. Methods: A comprehensive review of the literature regarding laser treatments for gynecological indications was performed based on several databases. Eligible were studies that included at least 15 patients. Outcomes: Several aspects, including preclinical data, have been investigated. For each topic covered, data on laser-based devices were analyzed. Results: Despite the high heterogeneity of studies and its limitations, the committee released several statements regarding the use of laser-based devices for genitourinary indications. Clinical Implications: Available data in the clinical setting are still poor, and the impact of these technologies on vaginal symptoms and signs has not been clearly established. Strengths & Limitations: All studies have been evaluated by a panel of experts providing recommendations for clinical practice. Conclusion: It is too early in the evolution and research of laser-based devices to make decisive recommendations regarding vaginal treatments. There is grave need to carry out randomized controlled trials with proper design for safety reasons, possible harm, and short-/long-term benefits for the different indications studied.